Annual Research Review: Adolescent mental health in the digital age: facts, fears, and future directions. (17th January 2020) - Odgers, Candice L.; Jensen, Michaeline R.
Abstract : Adolescents are spending an increasing amount of their time online and connected to each other via digital technologies. Mobile device ownership and social media usage have reached unprecedented levels, and concerns have been raised that this constant connectivity is harming adolescents' mental health. This review synthesized data from three sources: (a) narrative reviews and meta‐analyses conducted between 2014 and 2019, (b) large‐scale preregistered cohort studies and (c) intensive longitudinal and ecological momentary assessment studies, to summarize what is known about linkages between digital technology usage and adolescent mental health, with a specific focus on depression and anxiety. The review highlights that most research to date has been correlational, focused on adults versus adolescents, and has generated a mix of often conflicting small positive, negative and null associations. The most recent and rigorous large‐scale preregistered studies report small associations between the amount of daily digital technology usage and adolescents' well‐being that do not offer a way of distinguishing cause from effect and, as estimated, are unlikely to be of clinical or practical significance. Implications for improving future research and for supporting adolescents' mental health in the digital age are discussed. Abstract : Read the Commentary on this article at doi: 10.1111/jcpp.13219